2012
DOI: 10.1007/s00606-012-0615-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the monophyly of polyploid Gossypium species

Abstract: The origin and monophyly of the polyploid cotton (Gossypium) species has been largely accepted, despite the lack of explicit phylogenetic evidence. Recent studies in other polyploid systems have demonstrated that multiple origins for polyploid species are much more common than once thought, raising the possibility that Gossypium polyploids also had multiple origins, as postulated by some authors. To test the monophyly of polyploid cotton, we sequenced a 2.8-kb intergenic region from all diploid species belongi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 42 publications
3
50
1
Order By: Relevance
“…AD-genome tetraploids combined an A-genome donated by the maternal diploid parent and a D-genome from the pollen parent (Galau and Wilkins 1989;Wendel 1989;Wendel and Cronn 2003). A recent study (Grover et al 2012) demonstrated that the D-genome species G. raimondii and an A-genome species much like modern G. arboreum and G. herbaceum were involved in the creation of the polyploid species, and that this single combination gave rise to the polyploids. The present results also provide direct evidence for the monophyletic origin of polyploid Gossypium species.…”
Section: Discussionmentioning
confidence: 99%
“…AD-genome tetraploids combined an A-genome donated by the maternal diploid parent and a D-genome from the pollen parent (Galau and Wilkins 1989;Wendel 1989;Wendel and Cronn 2003). A recent study (Grover et al 2012) demonstrated that the D-genome species G. raimondii and an A-genome species much like modern G. arboreum and G. herbaceum were involved in the creation of the polyploid species, and that this single combination gave rise to the polyploids. The present results also provide direct evidence for the monophyletic origin of polyploid Gossypium species.…”
Section: Discussionmentioning
confidence: 99%
“…38 Ó 2015 Elsevier Inc. All rights reserved. Gossypium is a remarkably diverse genus, with over 50 recog-44 nized species divided into 8 diploid genome groups (Endrizzi 45 et al, 1985;Wendel and Grover, 2015) and a single, monophyletic 46 (Grover et al, 2012) (Grover et al, 2014). 60 While the genus itself has a relatively broad aggregate distribu-61 tion in the arid to sub-arid tropics and subtropics (Wendel and 62 Cronn, 2003;Wendel and Grover, 2015), the native distribution 63 of allopolyploid cotton is much narrower.…”
Section: Cotton 23mentioning
confidence: 98%
“…The two natural allopolyploid species G. hirsutum and G. barbadense represent divergent branches from a monophyletic allopolyploidization event that occurred 1-2 million years ago Grover et al 2012b). With both allopolyploids exhibiting the notable morphologic trait of long, spinable cotton fibers, it has long been hypothesized that allopolyploid cotton preferentially displays the physiologic profile and molecular machinery of its A-genome progenitor because it is in this genomic group that long fiber first evolved.…”
Section: Divergent Proteomic Development Following Allopolyploidizationmentioning
confidence: 99%
“…One key advantage of this system is that we could select a relatively simple morphologic structure for evolutionary analysis, namely, the single-celled epidermal trichome colloquially termed cotton "fiber." A second advantage is that we were able to simultaneously study two natural allopolyploid species, Gossypium hirsutum (AD 1 ) and G. barbadense (AD 2 ), that diversified from the same polyploidy event approximately 1-2 million years ago (Grover et al 2012b;Wendel et al 2012) and that were independently domesticated in parallel at least 5000 years ago . These allopolyploids were studied in parallel relative to models of their diploid progenitors, the A-genome species G. arboreum (A 2 ) and the D-genome species G. raimondii (D 5 ).…”
mentioning
confidence: 99%